PERMANOVA_data_within-analysis - Wellbrock, Arndt H.J.; Bauch, Christina; Rozman, Jan; Witte, Klaudia (Dryad Digital Repository, 2017)
This file includes geolocation data of repeatedly tracked individuals for permutational multivariate analysis of variance.